Type 1 pulmonary epithelial cells: a new compartment involved in the slow phase of particle clearance from alveoli. Issue 3 (May 2012) - Maynard, Robert L.; Donaldson, Kenneth; Tetley, Teresa D.
Abstract Whilst alveolar macrophages normally clear micron-sized particles from the respiratory units, nanoparticles might by-pass this mechanism and interact with alveolar epithelium. This letter discusses the possible role of alveolar epithelial type 1 cells in uptake and retention of nanoparticles within the alveolar septum. Accelerated apoptosis of nanoparticle-laden type 1 cells might trigger pro-inflammatory responses during apoptotic cell removal by macrophages. In the absence of clearance of apoptotic type 1 cells by this route, release of nanoparticles by dead type 1 cells and continued retention within the alveolar septum could lead to a slow process of nanoparticle removel from within the alveolar septum, rather than surface-only clearance. We suggest that this hypothesis warrants further research.